Queer Perspectives in New Music - Dharmoo, Gabriel; Brosin, Annette; R. Green, Anthony; Nickel, Luke; Doolittle, Emily; Henry, Symon; Kasahara 笠原 貞野, Teiya (Circuit)

(untitled) (Circuit, musiques contemporaines, 2021)
This collection of texts investigates how queerness manifests in contemporary new music practices. Six contributions by queer artists (Annette Brosin, Anthony R. Green, Luke Nickel, Emily Doolittle, Symon Henry and Teiya Kasahara 笠原 貞野) are framed by an introduction and conclusion by Gabriel Dharmoo. Dharmoo’s definition of queerness expands beyond sexual orientation and gender identity; it entertains the notion of queerness as an anti-assimilationist stance that defies normalcy, breaks down binaries and reveals the wideness of spectrums. As each statement illuminates how a marginalized experience as queer can profoundly inform ways of conceptualizing, creating, disseminating and understanding artistic output, this range of perspectives aims to broaden our understanding of queerness not only as an identity, but also as an artistic epistemology in and of itself.